Implementasi Program Baca Tulis Qur’an Melalui Metode Iqra dalam Meningkatkan Kemampuan Baca Tulis Qur’an Peserta Didik di RA Alhamidiyah - Jenal Abidin; Ai Teti Wahyuni; Ema Hanapiah; Eni Nuraeni (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
The introduction of learning to read and write the Al-Qur’an is one of the musts that must be given to early childhood as part of the Muslim community. Al-Qur’an as the holy book of Muslims acts as a source of law, the basis of knowledge and as a benchmark in the formation of early childhood behaviour, trough learning the basics of the Al-Qur’an such as reading and writing it, the child gets to know the good values contained in the Al-Qur’an. The formation of religious characters is through learning the Qur’an, one the wich is being able to read and write. The Qur’ani religious and personal character are needed in forming a civilized nation. The research was conducted the aim of knowing how to learn to read and write the Al-Qur’an properly and it should be for early childhood. The method used in this research is descriptive qualitative with a literature study appoarch. Data collection techniques in this study were carried out by collecting and analizyng primary data sources from books, articles and research results that have been conducted by previous researchers. The data analized is relevant to research on learning to read and write Al-Qur’an for early childhood. The findings from several references ilustrare how the implementation of learning to read and write Al-Qur’an for early childhood.